Deubiquitination and stabilization of programmed cell death ligand 1 by ubiquitin‐specific peptidase 9, X‐linked in oral squamous cell carcinoma - Jingjing, Wu (Cancer Med, 2018)
BACKGROUND: The immune checkpoint protein programmed cell death ligand 1 (PD‐L1) binds to PD1 to promote tumor cell escape from the killing effect of the immune system. However, there are few studies on the regulatory mechanisms of PD‐L1 in tumors. Although PD‐L1 has been reported to undergo ubiquitination in some cancers, its regulatory mechanisms in oral squamous cell carcinoma (OSCC) are unclear. Therefore, we aimed to investigate this phenomenon. METHODS: We examined the expression and function of USP9X and PD‐L1 in human oral keratinocytes (HOK) and OSCC cell lines (HN4 and HN30) as the control and relevant cancer cells using western blotting, immunoprecipitation, immunohistochemistry (IHC), T‐cell‐mediated tumor cell killing assay, and liquid chromatography‐mass spectrometry. RESULTS: Programmed cell death ligand 1 was highly expressed in OSCC by the regulation of the ubiquitin‐proteasome pathway. Furthermore, we discovered that ubiquitin‐specific peptidase 9, X‐linked (USP9X) could be combined with PD‐L1 to induce its deubiquitination and stabilize its protein expression in OSCC. CONCLUSION: Our data indicate that USP9X deubiquitinates and stabilizes PD‐L1. Suppressing the expression of USP9X blocks tumor cell growth. The results provide a theoretical basis for USP9X as a therapeutic target.